Compliance to Antihypertensive Medication and Associated Factors among Hypertensive Chronic Kidney Disease Patient Attending at a Tertiary Care Level Hospital - Parvin, Shahina; Parvin, Shahnaz; Nasrin, Shamima; Akter, Nargis; Afroz, Rozina; Sharmin, Rizwana; Sultana, Papiya; Fatema, Syeda Kaniz (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Achieving optimal blood pressure control remains a challenge in hypertensive chronic kidney disease patients, however monitoring and improving medication compliance would be a very useful tool to improve outcomes and to reduce the risk of complications like end-stage renal disease, cardiovascular disease and cerebrovascular accidents. Factors associated to compliance have importance for successful treatment of patients to prevent jeopardize of the goal of treatment. Objectives: To determine the proportion of treatment compliance among hypertensive chronic kidney disease patients. Method: An observational cross-sectional study was conducted in the department of Nephrology of Dhaka Medical College Hospital from January 2022 to December 2022. 264 hypertensive CKD patients were included in this study. Structured questionnaire was used to collect patients information like socio-demographic and behavioral characteristics, clinical history and prescribed antihypertensive medication. Collected data analyzed by using SPSS 26.0. P value of < 0.05 was significant. Result: Among 264 CKD patients 58% male, 42% female and 27.3% patients were in 51-60 years age group. Only 32.1% patient achieved BP (<140/90 mm of Hg) control with antihypertensive therapy and 36.7% patient received three drug combination therapy. Compliance to therapy was significant in patients with controlled BP and in patients who were taking three drug combination therapy (p = 0.001). 67.8% patient were compliant to antihypertensive therapy and significant association was found between regular intake of medicine to compliance (p=0.001). Patients who were taking table salt regularly (38.2%), smoker(18.9%), skipped medication because of feeling better(18.2%) , side effects(19.3%) and medication cost(4.1%) and physically inactive(28.1%) patients were noncompliant to therapy. This factors have significant association with medication compliance (p = 0.0001). Conclusion: Physical inactivity, smoking, regular table salt consumption, and medication side effects were common causes of patients' non-compliance. J Com Med Col Teachers’ Asso Jan 2025; 29(1): 32-36